Evolution of on-road vehicle exhaust emissions in Delhi. (March 2015) - Goel, Rahul; Guttikunda, Sarath K.
Abstract: For a 40-year horizon (1990–2030), on-road vehicle exhaust emissions were evaluated, retrospectively and prospectively, for the largest urban agglomeration in India – the Greater Delhi region with a combined population of 22 million in 2011 (Delhi along with Ghaziabad, Noida, Greater Noida, Faridabad and Gurgaon). Emissions of particulate matter, sulfur dioxide, carbon monoxide and volatile organic compounds (VOCs) reached their peak during late 1990s through early 2000s after which they reduced significantly through year 2012. On the other hand, nitrogen oxides (NOx ) and carbon dioxide show an increasing trend. The most reduction in emissions between 1998 and 2012 occurred as a result of implementation of four sets of vehicular emission standards, removal of lead, reduction of sulfur content, mandatory retirement of older commercial vehicles, and conversion of diesel and petrol run public transport vehicles to compressed natural gas. In addition, changes in the vehicular technology have also contributed to controlling emissions especially in case of auto-rickshaws and motorized two-wheelers, which changed from two-stroke to four-stroke. The rising trend of NOx along with the presence of VOCs indicates increasing tendency to form ground-level ozone and as a result, smog in the region. We predict that the current regime of vehicle technology, fuel standards, and high growth rate of private vehicles, is likely to nullify all the past emission reductions by the end of 2020s. Highlights: A 40-year retrospective and prospective analysis (1990–2030) of on-road emissions. On-road emissions for the largest urban agglomeration of India–Delhi. An update on vehicle and passenger travel characteristics based on primary surveys. Multi-pollutant emissions analysis and possible policy interventions for control.